Ischaemic heart disease following conventional and hypofractionated radiation treatment in a contemporary breast cancer series. Issue 3 (13th February 2018) - James, Melissa; Swadi, Sami; Yi, Ma; Johansson, Lisa; Robinson, Bridget; Dixit, Ashutosh
Abstract: Introduction: We report the incidence of ischaemic cardiac toxicity in a contemporary cohort of patients receiving conventional (CFRT) or hypofractionated (HFRT) radiation after surgery for early breast cancer and investigate the interplay of cardiac risk factors and fractionation. Methods: Included were patients receiving external beam radiation treatment from 2002 to 2006 at the Christchurch public hospital. Hospital coding databases, oncology databases and medical records were reviewed for baseline characteristics, treatment details and outcomes. The primary outcome was cardiac toxicity (including myocardial infarction, admission for cardiac chest pain, coronary angiogram positivity and ischaemic cardiac death). Kaplan‐Meier methods were used to derive ischaemic cardiac event free and overall survival. Predefined univariate and multivariate analysis was performed to investigate interaction with radiation fraction size, cardiac risk factors, age and side of cancer. Standardised mortality ratios were constructed. Results: Five hundred and one patients were identified, 220 treated with CFRT and 281 with HFRT. The median age was 56 and median follow‐up 10.33 years. The 10‐year breast cancer specific survival was 81.8% (95% CI %.78.1–85.0). The 10‐year freedom from cardiac death was 98.6% (95% CI 96.9–99.4). There were 27 post radiation cardiac events including 5 cardiac deaths and 19 cases of acute myocardial infarction. 265 (53%) had at least one cardiac risk factor. Twenty five of the 27 patients with a cardiac event had cardiac risk factors. On univariate and multivariate analysis, fractionation schedule was not significantly associated with a post radiation ischaemic event, however, there was a significant relationship with age and the presence of a cardiac risk factor. The standardised mortality ratio was 0.89 (95% CI: 0–3.13). Conclusions: Our study has shown a low rate of ischaemic cardiac disease for both CFRT and HFRT in women treated for breast cancer with no evidence of an effect with fractionation schedule. Coexisting cardiac risk factors are common in the population.